2016
DOI: 10.7203/relieve.22.1.8280
|View full text |Cite
|
Sign up to set email alerts
|

Ítems contextualizados de PISA Ciencias: La conexión entre las demandas cognitivas y las características de contexto de los ítems

Abstract: El uso frecuente de contextos en los ítems de la prueba se basa en la premisa de que la contextualización de ítems es una estrategia eficaz para comprobar si los estudiantes pueden aplicar o transferir sus conocimientos. En este trabajo, seguimos una línea de investigación que se centra en probar esta premisa. Se presenta un estudio de las características del contexto en una muestra de ítems de PISA ciencias de 2006 y 2009 y cómo estas características, así como el rendimiento del estudiante puede estar relacio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
(2 reference statements)
0
2
0
Order By: Relevance
“…A wealth of evidence speaks to the influence of different item features on the examinees' performance on tests. For example, we know that the performance of students is instable across item formats (Ruiz-Primo et al, 1993); that construct equivalence may vary depending on the ways in which items are designed (Rodriguez, 2003); and that even small changes in wording may cause translated items to function differentially (Ercikan et al, 2014).…”
Section: Items As Samples Of Encoded Cultural Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…A wealth of evidence speaks to the influence of different item features on the examinees' performance on tests. For example, we know that the performance of students is instable across item formats (Ruiz-Primo et al, 1993); that construct equivalence may vary depending on the ways in which items are designed (Rodriguez, 2003); and that even small changes in wording may cause translated items to function differentially (Ercikan et al, 2014).…”
Section: Items As Samples Of Encoded Cultural Experiencementioning
confidence: 99%
“…Contexts are very common in current large-scale assessment programs. For example, a study on the use of contexts in PISA 2006 and PISA 2009 items found that about one third of the sample of items examined contained contexts in the form of a narrative (Ruiz-Primo and Li, 2016).…”
Section: Contextsmentioning
confidence: 99%